CLINICAL EVALUATION OF STEM BARK POWDER OF SHIGRU (MORINGA OLEIFERA LAM.) IN DYSLIPIDEMIA (AYUSHDHARA, 2016)
In recent times drastic changes have taken place in dietary habits and mode of life style which has resulted in precipitation of various metabolic diseases. One such alarming condition, which is on a high rise in the society, is Dyslipidemia. Since the pathology has a clear link with a person’s life style, the body demands a more holistic approach in treatment, hence indigenous system of medicine especially herbal preparations can play major role in finding a safe, simple and cost effective solution for the management of Dyslipidemia. Shigru botanically identified as Moringa oleifera Lam. is one of such commonly available plant which is greatly praised for its Medoghna property in various Nighantus.A clinical study of Shigru twak (stem bark) was conducted on 30 patients at OPD level of Government Ayurveda College Hospital, Tripunithura, Kerala. Shigru stem bark powder (Choornam) was given in the form of capsule, in a dose of 3gm per day along with lukewarm water before food for a period of 45 days. Assessment based on blood lipid levels and clinical features was done before and after treatment. The results were statistically analyzed. After the intervention Total Cholesterol, Serum LDL, Serum VLDL, Serum Triglyceride and Body weight were significantly reduced. On symptomatic evaluation the drug was significantly effective in reducing heaviness of body, chest pain, excessive sleep, excessive sweating, and breathlessness on exertion, palpitation and lethargy. The study revealed that Shigru twak is safe and effective in Dyslipidemia.